1987
DOI: 10.1002/jcb.240350104
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of basement membrane matrix degradation by purified proteases and by metastatic tumor cells

Abstract: We have examined the nature of biochemical degradation of an isolated basement membrane matrix (bovine lens capsule) using different methodologies. The first strategy was quantitation of the release of surface-bound 125I and a second the documentation by SDS-PAGE of the appearance of putative cleavage products and the loss of high-molecular-weight components from the matrix. Basement membrane matrix bands resolved on SDS-PAGE were identified by their protease sensitivities as well as by Western immunoblots usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1989
1989
1997
1997

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…Indeed, it is well known that cellular migration is increased when the extracellular matrix of the cells is degraded by proteinases, as in the case of metastatic cells [Xie et al, 1994;Southgate et al, 1992]. Moreover, it has been shown that smooth muscle cell migration and proliferation are suppressed when metalloproteinases are inhibited by synthetic inhibitors [Starkey et al, 1987]. Thus, the increased turnover of collagen in the extracellular matrix could well enhance in vivo cellular movement and growth, hallmark features of early atherogenesis and restenosis.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it is well known that cellular migration is increased when the extracellular matrix of the cells is degraded by proteinases, as in the case of metastatic cells [Xie et al, 1994;Southgate et al, 1992]. Moreover, it has been shown that smooth muscle cell migration and proliferation are suppressed when metalloproteinases are inhibited by synthetic inhibitors [Starkey et al, 1987]. Thus, the increased turnover of collagen in the extracellular matrix could well enhance in vivo cellular movement and growth, hallmark features of early atherogenesis and restenosis.…”
Section: Discussionmentioning
confidence: 99%
“…Tumour cells produce and release type-IV-specific collagenases which function at neutral PH (Salo et al, 1983;Starkey et al, 1987;Irimura et al, 1987), but the micro-environment of the tumour-host junction may favour the activity of collagenolytic enzymes that act at acidic PH rather than at neutral PH.…”
mentioning
confidence: 99%
“…Indeed, experimental evidence indicates that there are multiple pathways associated with tumor cells [95]. Nevertheless, a general schematic can be suggested in which plasmin/plasminogen activator activate those latent metalloproteinases that are able to initiate degradation of the collagen matrix scaffolds.…”
Section: Matrix Degrading Enzymes Important To the Invasive/metastatimentioning
confidence: 99%